Green Human Resources Management in Industrial Companies on Sustainable Business: Conceptual Approach - Ayu Ambarwati; Dyah Wahyuni; Andini Jatsiya Dewi; Wira Kuswara; Retno Purwani Setyaningrum (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
Indonesia has the third lowest per capita CO2 emission in the world, which is 2.1 tons. Even so, the problem of increasing carbon emissions remains an important issue in Indonesia, mainly due to the presence of factories. Companies in Indonesia have made efforts to overcome this problem, one of which is through the implementation of Green Human Resource management (GHRM) or environmentally friendly based human resource management. The purpose of this scientific article is to explain the relationship between green resource management variables using theoretical and empirical approaches, as well as interviews with several respondents, in the context of business sustainability. The approach used in this study is a qualitative method. The results of this study reveal that the variables that affect Green Human Resource management, such as environmentally friendly-based recruitment, environmentally friendly-based training and development, environmentally friendly-based performance management and assessment, as well as environmentally friendly-based compensation and rewards, have an effect on business sustainability.